Identification of a locus near ULK1 associated with progression-free survival in ovarian cancer - Quinn, Michael C.J.; McCue, Karen; Shi, Wei; Johnatty, Sharon E.; Beesley, Jonathan; Civitarese, Andrew; O'Mara, Tracy A.; Glubb, Dylan M.; Tyrer, Jonathan P.; Armasu, Sebastian M.; Ong, Jue Sheng; Gharahkhani, Puya; et al. (Cancer Epidemiology Biomarkers & Prevention, 2021)
Background: Many loci have been found to be associated with risk of epithelial ovarian cancer (EOC). However, although there is considerable variation in progression-free survival (PFS), no loci have been found to be associated with outcome at genome-wide levels of significance. Methods: We carried out a genome-wide association study (GWAS) of PFS in 2, 352 women with EOC who had undergone cytoreductive surgery and standard carboplatin/paclitaxel chemotherapy. Results: We found seven SNPs at 12q24.33 associated with PFS (P < 5 × 10-8), the top SNP being rs10794418 (HR = 1.24; 95% CI, 1.15-1.34; P = 1.47 × 10-8). High expression of a nearby gene, ULK1, is associated with shorter PFS in EOC, and with poor prognosis in other cancers. SNP rs10794418 is also associated with expression of ULK1 in ovarian tumors, with the allele associated with shorter PFS being associated with higher expression, and chromatin interactions were detected between the ULK1 promoter and associated SNPs in serous and endometrioid EOC cell lines. ULK1 knockout ovarian cancer cell lines showed significantly increased sensitivity to carboplatin in vitro. Conclusions: The locus at 12q24.33 represents one of the first genome-wide significant loci for survival for any cancer. ULK1 is a plausible candidate for the target of this association. Impact: This finding provides insight into genetic markers associated with EOC outcome and potential treatment options.
CRIS-Team Scopus Importer:2021-09-10